HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT PADA LANSIA PENDERITA HIPERTENSI DI DESA LAUT DENDANG TAHUN 2024 - Meiman Arif Sarumaha; Jamila Rambe (Jurnal Riset Multidisiplin Edukasi, 2025)
Aging is a process experienced by everyone, marked by gradual decline in physical, social, and mental aspects that cannot be avoided. This type of research is quantitative with a cross-sectional survey design. The sampling technique used in this study is a non-probability sampling method, specifically purposive sampling, with a sample size of 54 respondents. Data analysis was conducted using Pearson correlation test. The results of this study, using the Pearson correlation test, indicate a significant relationship between family support and medication adherence, with a p-value of 0.825 (α < 0.05). It is hoped that the future researchers will further develop this study, and the findings can serve as a source of information to enhance understanding of the relationship between family support and medication adherence among elderly individuals with hypertension. Future researchers are also advised to conduct similar studies using different methods, such as experimental or qualitative approaches.